The safety and efficacy of endoscopic ultrasound-guided portal pressure gradient measurement with concomitant endoscopic ultrasound-guided liver biopsy: a systematic review - Malik, Alexander; Yousaf, Muhammad Nadeem; Hammoud, Ghassan M. (Frontiers in Gastroenterology, 2023)
Introduction Portal hypertension (PH) is a complication of advanced liver disease. Traditionally, PH has been quantified using hepatic venous pressure gradient (HVPG) through an indirect transjugular approach requiring ionizing radiation exposure. Endoscopic ultrasound-guided porto-systemic pressure gradient (EUS-PPG) measurement is an emerging alternative, minimally invasive technique that provides direct portal pressure measurement. The aim of this systematic review is to evaluate the safety and efficacy of EUS-PPG measurement and concomitant EUS-guided liver biopsy (EUS-LB) in patients with chronic liver disease. Methods The preferred reporting items for systematic reviews and meta-analyses method was used. A PubMed, Medline, Web of Science, Google Scholar, and CINAHL search for terms “endoscopic ultrasound,” “EUS,” and “portal pressure gradient” was used to identify qualifying studies. Eligible studies included those which were published before 2022, reporting outcomes of EUS-PPG measurement, simultaneous EUS-LB if applicable, and adverse events rate. Risk of bias was assessed by Egger’s test. Results were synthesized using I2 to test heterogeneity. Results Four published studies including 147 patients met inclusion criteria, with mean age 59.6 years, 59% male. Indications for EUS-PPG measurement were history of chronic liver disease or suspected cirrhosis, viral hepatitis, alcohol associated liver disease, hepatic sinusoidal obstruction or Budd Chiari syndrome. The pooled technical success rate of EUS-PPG measurements was 98.61% with 95% confidence interval of 95.20% - 99.82%. A 25-gauge needle was used in 92% (135/147) of patients. EUS-PPG measurement was performed through a transgastric approach in all 147 (100%) patients using a compact manometer with pressure transducer and non-compressible tubing. The mean PPG was 10.07 (range 6.44 – 13.70) mmHg. Ninety-five patients underwent simultaneous EUS-LB using 19G needle with wet suction technique. Technical success rate of EUS-LB was 100% and specimen was adequate in 99% (94/95) patients to establish histological diagnosis. There were no major life-threatening complications of the EUS-PPG procedure. Predominant adverse events were abdominal pain 6.1% (9/147) and sore throat 5.4% (8/147). Conclusion EUS-PPG measurement is safe and useful in providing an assessment of portal pressure in patients with chronic liver disease. Future studies are needed to evaluate whether there is consistent correlation between EUS-PPG measurements and histologic fibrosis stage by liver biopsy.